Alinhamento do processo de terceirização em uma indústria off shore - Gonçalves, Carlos Eduardo Pereira (2006)
The work developed in this thesis analyzes the outsourcing process in PETROBRAS,Bacia de Campos Unit - UN-BC, Surface Installation area - ISUP. Through the accomplished research, it was lifted up the report of the evaluations of the Bulletins of Performance Evaluation - BAD in two types of contracts of Construction and Assembly: The "Conventional" and the "Family" contracts, which represents a new type of "Umbrella" contracts. The research has as general objectives to make concepts and to develop administration strategies for outsourcing in the C&M and maintenance areas.Specifically, the work presents a methodological proposal with base in past results reports, for application in the bidding process and in the terms of contractual instruments, regarding the services rendered by outsourcing companies, in order to obtain the leveling of the managerial actions, focused in common values between outsourcing companies and the contracting party, for the reach of the business goals